The Role of New Communication in Promoting Human Rights in Jordan - Al Hadeed , Ali Yahya Bader; Shatnawi , Ghaleb Ali; Al-Zoubi , Ashraf Faleh; Tahat, Zuhair Yassin; Olimat, Farhan Rashed (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to identify the role of modern communication in promoting human rights in Jordan and the role of the electronic pages of Jordanian institutions concerned with human rights in spreading the culture of human rights in Jordan. Method: The study is of a qualitative nature that relies on observation and in-depth interviews with a sample of (4) academic professors in the field of media and law. Results: The means of new communication have an important and significant role in promoting human rights, and the most important of these means is represented by social networking sites (Facebook, Twitter, YouTube and Instagram) and then search engines in general in the Internet, and then forums, and blogs. It turns out that the most important human rights of modern communication in Jordan are the rights related to women and children, political rights related to elections and parties, and justice and equality. Further, it turns out that the web pages of human rights institutions in Jordan play a good role, and that they provide content related to many issues that affect and touch on human rights. Conclusion: It is clear that the importance of modern means of communication stem from promoting human rights in Jordan and the world at large, and that it has been able to detect many violations that human beings have been subjected to in various parts of the world.